Fungicides and Biological Products Activities towards Fungi Causing Diseases on Banana and Vegetable in Cote d'Ivoire - Koné, Daouda; Brahima, Camara; Odjochounou, Badou Jean; Mohamed, Doumbouya; Sibirina, Soro; N'Guessan, Carine Aya; Lezin, Bomisso Edson (IntechOpen, 2010)
None